Working together: A study of civil society partnerships between WASH (water, sanitation, and hygiene) and GESI (gender equality and social inclusion) organisations in Timor-Leste - Grant, Melita Louise; Nguyen, Therese Tam; Vieira, Ajerino; Niner, Sara Louise; Roche, Chris (Frontiers in Water, 2023)
This article reports on an empirical study conducted in Timor-Leste that explored the drivers, benefits, and challenges of partnerships and collaborations between water, sanitation, and hygiene (WASH) and gender equality and social inclusion (GESI) organisations as integral parts of the WASH system. Key drivers to form partnerships were found to be the identification of community WASH service gaps and the alignment of advocacy agendas. Key benefits reported were increased inclusion and empowerment outcomes and strengthened organisational knowledge and capacity. Challenges emerge when organisations’ key staff change, strategies misalign, and financial and administrative capabilities differ. The study contributes practical insights into how civil society organisations (CSOs) partner to strengthen mutual WASH and GESI strategies and programmes and their outcomes. The research design was primarily qualitative and included a data-collection workshop with 30 CSO representatives from 16 organisations in Dili, longitudinal research involving semi-structured interviews over 2.5 years, and two rounds of interviews with five organisations and semi-structured interviews with an additional 18 CSOs. We applied a framework of post-development theory, including critical localism and working contingently. The study recommends strengthening the partnerships between WASH and GESI organisations in ways that are cognisant of power dynamics, local priorities, and capacity needs and promote longevity and continuity through ownership of decisions at the local level. Our findings suggest that meaningful, reciprocal, and respectful engagement with WASH and GESI organisations allows WASH programmes to be in a better position to address the harmful norms that drive inequitable behaviours, thus strengthening the WASH governance system overall.